The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1038/s41598-019-53705-1
|View full text |Cite
|
Sign up to set email alerts
|

Redox activation of JNK2α2 mediates thyroid hormone-stimulated proliferation of neonatal murine cardiomyocytes

Abstract: Mitochondria-generated reactive oxygen species (mROS) are frequently associated with DNA damage and cell cycle arrest, but physiological increases in mROS serve to regulate specific cell functions. T3 is a major regulator of mROS, including hydrogen peroxide (H2O2). Here we show that exogenous thyroid hormone (T3) administration increases cardiomyocyte numbers in neonatal murine hearts. The mechanism involves signaling by mitochondria-generated H2O2 (mH2O2) acting via the redox sensor, peroxiredoxin-1, a thiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(55 citation statements)
references
References 45 publications
0
54
1
Order By: Relevance
“…T3-receptor α (TRα) mediates the proliferative action of T3 in murine neonatal (P2) cardiomyocytes by activation of IGF-1/IGF-1R 12 , which involves Ras/Raf/MAPK kinase (MEK)/ERK signaling 9 . MEK1/2 activates ERK1/2 by phosphorylating T202 and Y204 9 , which is required for ERK1/2 translocation to the nucleus 10 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…T3-receptor α (TRα) mediates the proliferative action of T3 in murine neonatal (P2) cardiomyocytes by activation of IGF-1/IGF-1R 12 , which involves Ras/Raf/MAPK kinase (MEK)/ERK signaling 9 . MEK1/2 activates ERK1/2 by phosphorylating T202 and Y204 9 , which is required for ERK1/2 translocation to the nucleus 10 .…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we have shown that exogenous T3 stimulates cardiomyocyte proliferation in P2 murine hearts. These cardiomyocytes are immature and are capable of proliferating in response to growth factors and injury 12 , 17 , 18 . After P6, however, cardiomyocytes do not proliferate in response to injury 18 and are resistant to growth factor-induced cell proliferation 17 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations